LOCALIZATION FEATURES OF URANIUM MINERALIZATION IN THE TASIAST-TIJIRIT TERRANE, THE REGUIBAT SHIELD - Sydorchuk, V.; Zagnitko, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The Reguibat Shield is an area of intensive uranium exploration and about 80 ore occurrences have been discovered in recent decades within its borders. The region of the study is located within the Tasiast-Tijirit terrane, which represents a northwestern part of Archean domain of the Reguibat Shield. The rocks of the terrane are of Mesoarchean age. The main types of rocks are migmatites, gneisses and amphibolites, greenstone associations, granitic intrusions and pegmatites. Samples of pegmatites, granites, ferruginous quartzites and sedimentary rocks that showed an increased radiation level after conducting a ground-based radiometric survey were selected for laboratory studies from the host rocks of the Tasiast-Tijirit terrane. The following types of laboratory analyses were used for the study: 1) spectral analysis by laser-luminescence method to determine the uranium content in samples; 2) atomic emission spectroscopy for the general estimation of concentrations of chemical elements in samples; 3) X-ray fluorescence analysis to determine the chemical composition of samples and its trace elements; 4) electron microprobe analysis to determine the morphology of mineralization and the chemical composition of uranium minerals. Among the Tasiast-Tijirit terrane rocks the increased uranium content was found in the following rock associations: pegmatites and granites; ferruginous quartzites within the banded iron formation; calcretes in sedimentary rocks. According to the results of field and laboratory studies, the main factors of the localization of uranium mineralization in calcretes of the OumDherua area were established. The main geological, physical and chemical conditions essential for the formation of uranium mineralization of the calcrete type within the study region were established. It was found that granites and pegmatites could provide source of uranium for ore mineralization in sedimentary formations, such as surficial and calcrete types. The latter are studied and mined quite intensively in the world including the Reguibat Shield. The study results show the high potential for prospecting and exploration of new uranium occurrences within the Tasiast-Tijirit terrane.